PENGGUNAAN PERANGKAP KUNING BERDASARKAN BENTUK DAN BEBERAPA KETINGGIAN PERANGKAP TERHADAP HAMA Liriomyza spp. (Diptera: Agromyzidae) PADA TANAMANBAWANG MERAH (Allium ascalonicum L.) - Rio A A Sinubulan; Darma Bakti; Mena Uly Tarigan (Universitas Sumatera Utara, 2013)
Yellow traps is one of mechanical control leaf miner (Liriomyza spp) on shallolt(Allium ascalonicum (L.). This study was conducted in Desa Batukarng located at the altitude of about1,100 meters above sea level.The purpose of this study was to fine out the influence of the use severalforms and altitude of yellow. Trap on Liriomiza spp ( leaf-slitting fly) as the pest on shallot(Allium ascalonicum (L.). This study employed the Non-Factorilal Group Random Design Methodwith 7 treatments and 3 repetitions by using yellow square and cylindrical trap set at the latitude of10,30,50 cm above the ground. The result of this study showed that the average number of pets trappedhad a significant influence on the population of Liriomyza spp ( leaf-slitting fly) at shallot plantingground of square treatment with height of 10 cm. The form and height of trap had a very significantinfluence on percentage of Liriomyza spp attack to the square treatment with the height of 10 cm.Based on the result of the study, it is found out the square trap with the height of 10 cm is moreeffective to control the population of Liriomyza spp.Key words: shallot , leaf- slitting, yellow trap.